Relatório de Estágio Profissional "O Desafio de Ser Professora" - Catarina da Silva Guedes (2017)
The internship's year presents itself as the climax of the training for teaching, materialized in the practice of supervised teaching. This practice allows the student the cross-check with reality and the opportunity to put into practice the knowledge acquired. Through supervised practice, the future teacher has the time to take risks, seek to overcome his personal challenges and go through a teaching experience in the real context, sometimes unknown up to that moment. The internship took place in a school located in the city of Espinho, belonging to the district of Aveiro, with the advice of a cooperating teacher and a teacher who guided the course taken during the school year. This document is divided into five major chapters: (1) Personal level, which reports the biographical trajectory of the student-trainee; (2) Professional Practice Framework, in which the context of the practice is described and interpreted: (3) Organization and teaching learning management - divided into three areas: design, planning and implementation; (4) Participation in School and Community Relations; (5) Professional development. In this last chapter, the research study is incorporated: "Functional training in the context of physical education classes: study in a high school class" applied in a twelve grade class. At the end of the document, in the form of a conclusion, the emotions experienced during the internship year are highlighted.